The Efek Pemilihan Saluran Distribusi Digital Pada Keputusan Pembelian Produk UMKM Garmen di Kota Semarang - ASTUTI, YANTI PUJI; Rinwantin, Rinwantin (EconBank: Journal of Economics and Banking, 2024)
Digital marketing does not just talk about promotions or advertising but also includes distribution channels. The choice of distribution channels by producers has an impact on purchasing interest and subsequently on consumer purchasing decisions. In connection with distribution, product availability also influences consumer purchasing interest and purchasing decisions. Digitalization efforts to increase the capacity of MSMEs face the challenge of understanding digital marketing. This research aims to provide insight into the influence of digital on purchasing decisions. A total of 100 people were taken as samples using purposive sampling. The data analysis technique used in this research is PLS-SEM. The research results found that digital distribution channels and product availability have a positive and significant impact on purchasing interest and purchasing decisions. The mediating effect of purchasing interest on the relationship between distribution channels and product availability on purchasing decisions is also proven empirically. Purchasing decisions can be increased through purchase interest by increasing digital distribution channels by MSME players. Policies in product availability can also increase purchasing decisions through purchase interest. MSME players are expected to be able to provide more variety in digital distribution channels and increase the availability of relatively more complete products